2013
DOI: 10.1039/c2sm26448j
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity, dielectric anisotropy, and birefringence in the nematic phase of three four-ring bent-core liquid crystals with an L-shaped molecular frame

Abstract: Molecular shape is an important factor in determining the material properties of thermotropic liquid crystals (LCs). We synthesized and investigated several LC compounds formed by asymmetrically bent molecules with a rigid four-ring core in the shape of the letter 'L'. We measured the temperature dependencies of dielectric permittivities, birefringence, splay K 1 and bend K 3 elastic constants, splay viscosity h splay and flow viscosities h || and h t . The bend-splay anisotropy dK 31 ¼ K 3 À K 1 is negative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 64 publications
2
34
0
2
Order By: Relevance
“…[15,18,19,22,23,74] and calculations have shown that it can be ascribed to the bent molecular shape. The most relevant feature is that K 3 is smaller than K 1 and remains almost constant over a wide temperature range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15,18,19,22,23,74] and calculations have shown that it can be ascribed to the bent molecular shape. The most relevant feature is that K 3 is smaller than K 1 and remains almost constant over a wide temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…[17]. [69][70][71] Very recently, the temperature dependence of the elastic constants was measured for the nematic phase of a number of bent-shaped mesogens, [18][19][20][21][22][23][72][73][74] with results similar to those for A131. For the bend-elastic constant, theoretical predictions are in good agreement with the experimental trend in the temperature region far from the smectic C transition: K 3 < K 1 is found, with K 3 scarcely dependent on temperature.…”
Section: Elastic Constantsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although γ was increased by mixing BLC in most of the previous literature [34], our result showed a reduction of γ after doping BLC. Avci et al recently reported that BLC with an asymmetric shape could show relatively low viscosity [35]. Thus, γ is certainly deeply related to the structure of BLC.…”
Section: Resultsmentioning
confidence: 98%
“…BCNs usually exhibit low-frequency dielectric relaxation and have an in verted, K 33/K ]] < 1, elastic ratio; their viscosities can be three orders of magnitude higher compared to rodlike compounds [26,[28][29][30][31]. These special characteristics of typical BCNs are attributed to their bent molecular shape, the resulting preference for a polar ordering and thus the presence of cybotactic smectic clusters [32][33][34][35][36].…”
Section: Measurement Of Materials Parametersmentioning
confidence: 97%